2021
DOI: 10.1155/2021/7253633
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Four Autophagy-Related Genes Accurately Predicts the Prognosis of Gastrointestinal Cancer in Asian Patients

Abstract: Gastrointestinal (GI) cancers are among the most fatal diseases in the world. Numerous studies have demonstrated the relationship between autophagy and development of gastrointestinal cancers. However, whether autophagy-related genes can predict prognosis of GI cancers in individuals of Asian ancestry has not been defined. This study, evaluated the prognostic value of autophagy-related genes in gastrointestinal cancer. Expression profile of autophagy-related genes for 296 gastrointestinal cancer patients of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The Kaplan–Meier survival plot also confirmed that our model with the lowest p -value has the best ability to distinguish prognosis ( Figures 4D–F ). In addition, through the comparison of the c-indexes, we also observed that our model performed better than the model of Tang et al (2021) ( Figure 4G ). And our model has also been marked to have the highest RMST curve in 3 models ( Figure 4H ).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…The Kaplan–Meier survival plot also confirmed that our model with the lowest p -value has the best ability to distinguish prognosis ( Figures 4D–F ). In addition, through the comparison of the c-indexes, we also observed that our model performed better than the model of Tang et al (2021) ( Figure 4G ). And our model has also been marked to have the highest RMST curve in 3 models ( Figure 4H ).…”
Section: Resultssupporting
confidence: 54%
“…After multiple analysis and verification of multiple internal and external datasets, our model has proven to meet this requirement. In addition, our model showed the best predictive value compared with other models in previous research (Song et al, 2021;Tang et al, 2021). Three PR-DE-IRFeGs have been reported to be closely related to ferroptosis and immunity, as well as the occurrence, development and prognosis of certain cancers.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations